Use ultra wideband communication systems for increase of speed of data transmission - Дрововозов, В. І.; Бригинець, О. М. (Problems of Informatization and Control, 2011)
To increase the speed of wireless transmission of multimedia and bulk files between computer and its peripherals ultra wideband technology UWB are considered. The advantages and disadvantages of the use of UWB technology for quick and reliable communication in wireless networks are analyzed